Foreign direct investment, trade and economic development: An overview - Michael Blanga-Gubbay; Stela Rubínová (World Trade Organization (WTO), 2023)
This paper explores the dynamic relationships between foreign direct investment (FDI), international trade, and economic development. First, emphasizing the pivotal role of multinational enterprises (MNEs) - particularly in the context of Global Value Chains (GVCs) - it underscores how FDI and trade are mutually reinforcing. Then, it highlights the convergence of investment and trade policies, pointing out the impact of Bilateral Investment Treaties (BITs) on trade flows and the increasing inclusion of investment provisions in Regional Trade Agreements (RTAs). Third, examining global FDI trends, it shows that developing and emerging economies are still lagging behind, but they are fast growing in importance. Finally, it draws on a rich empirical literature to show how FDI drives economic development through knowledge spillovers, technology transfer, and export upgrading.
Keywords: F21; F23; O19; 330; foreign direct investment; international trade; economic development